Trade and competitiveness of African sugar exports - Mabeta, Joshua; Smutka, Luboš (Frontiers in Sustainable Food Systems, 2023)
Introduction Sugar ranks among the most widely consumed, traded, sensitive, and protected commodities on the global and intra-regional stages. Recent developments in the sugar industry, inclusive of price distortions in the global sugar market, the liberalization of the European sugar sector, and the globalization of international agricultural trade, have amplified the need to comprehend the evolution of competitiveness in African sugar exports. Consequently, this study aims to provide a comprehensive analysis of the patterns, trends, and shifts in the inter- and intra-regional competitiveness of African sugar exports. Methods This paper employed the Normalized Revealed Comparative Advantage (NRCA) index and the Harris-Tzavalis panel-data unit-root test to assess the stability and structural changes in the competitive patterns of sugar exports for 34 African countries. The analysis is based on panel data spanning the period from 2001 to 2021. Results and discussion The NRCA indices unveil certain dynamics and shifts in the competitiveness of country-specific sugar exports. Overall, the number of countries exhibiting competitive sugar exports has marginally increased, rising from 14 in 2001 to 17 in 2021. However, only eight African countries, predominantly from the southern region, have consistently maintained competitiveness in both the global and intra-regional markets throughout the entire analysis period. A significant portion of sugar exports from African countries has remained non-competitive on the global market, with a select few oscillating between periods of comparative advantage and disadvantage. Notably, the North African nations of Morocco, Algeria, and Egypt have transitioned from a position of comparative disadvantage to one of comparative advantage. At the intra-regional level, the presence of tariff and non-tariff trade barriers, including tariff escalations and trade embargoes, has rendered sugar exports non-competitive. These barriers augment the challenges faced by producers in other African nations seeking to exploit economies of scale. Conclusion The sustained competitiveness of sugar exports from the Southern African region to other African regions underscores the significance and increasing impact of Foreign Direct Investment (FDI) in bolstering the competitiveness and development of the sugar industry.